LT22 Radio La Colifata - Larrondo, Carlos (Bausan Films ; Filmanova, 2007)
Verzio FF Submission LT22 Radio La Colifata is a radio station run entirely by the patients of the J.T. Borda Psychiatric Hospital in Buenos Aires. Recorded and broadcast from the hospital gardens, it is heard the world over. It is a station that questions the border between madness and reason, a station that breaks down the dividing wall between the “sane” and the “mad”. It gives the word to people whose voice has been denied for too long - “the mad” -, who can also show us the many things that we, the “sane”, are incapable of seeing.